Sulfonated Polystyrene Pore-Filled Electrolytes Membranes By Electrons Induced Grafting Of Styrene Into PTFE Films : Thermal Stability And Structural Investigation - Zubir, N. A.; Ismail, A. F.; Nasef, M. M.; Dahlan, K. Z. M.; Saidi, H. (2004)
The thermal stability and structural investigation of sulfonated polystyrene pore-filled electrolyte PTFE membranes prepared by radiation grafting of styrene into porous PTFE films and the subsequent sulfonation, were studied via using thermal gravimetric analysis and differential scanning calorimetry, respectively. A three-step degradation pattern was observed from TGA thermograms of all the membranes, which attributed to the dehydration, desulfonation, and degradation of the PTFE backbone. The weight losses in the membranes were found to be reliant on the grafting yield, whilst the degradation temperatures were shown to be independent of the grafting yield. The intrinsic crystallinity of the PTFE matrix was found to exhibit a decreasing trend with increasing in the grafting yield. A further decrease in crystalilinity was also observed in the sulfonation reaction. The residual crystallinity of the PTFE matrix approximately 11% was still remained in the membranes even after subjected to severe reaction conditions. The decreased in crystallinity of the resulting membranes can be explained by the combination of the dilution effect and the crystal disruption which occurred within the membranes matrix.